Población folicular y concentraciones plasmáticas de progesterona (P4) en ovejas sometidas a diferentes protocolos de sincronización - Uribe-Velásquez, L. F.; Oba, E. [UNESP]; Souza, M. I.L. (My University, 2008)
The effect of prostaglandin (PGF2α) vs CIDR and eCG (equine corionic gonadotrophin) on dynamic of follicular population and its relationship with P4 plasma concentrations were investigated in cyclic ewes. Fourteen Bergamascia ewes were used, Group 1 was synchronized using two i.m. injections of PGF2α and Group 2 treated for 14 d with CIDR and 500 IU of eCG at dispositive withdrawal on day 14. Ovarian follicular dynamics were ultrasonically monitored. All ovarian follicles ≥ 2 mm were measured, and their relative locations were recorded on an ovarian map in order to follow the sequential development of each individual follicle. Blood samples for P4 determination were collected daily starting the day before the second injection of PG2α (G1) and from administration of eCG (G2) until day 10 after ovulation of the cycle. There were significant (P<0.001) differences in P4 plasma concentrations among treatments. The CIDR + eCG (500 IU) treatment increased the recruitment of smaller follicles and the maximum diameter and growth rate of large follicles during the first wave.
Follicular population and progesterone (P4) plasma concentrations in sheep under different synchronization protocols
Keywords: Follicular dynamics; Progesterone (P4); Ultrasonography ovine